Silica Aerogel-supported Hydrozincite and Carbonate-intercalated Hydrotalcite for High-efficiency Removal of Pb(II) Ions by Precipitation Transformation Reactions - Wang, Lijun (Nanoscale Res Lett, 2017)
In this work, hydrozincite and Zn/Al-CO(3) (2−) hydrotalcite supported on silica aerogel were prepared via a simple and economical process and used as adsorbents for Pb(II) removal. The supported hydrozincite and Zn/Al-CO(3) (2−) hydrotalcite possess ultra-thin thickness, high surface area, and weak crystallinity. In the batch Pb(II) adsorption experiments, the adsorbents with higher Zn(II) contents showed higher Pb(II) adsorption capacities, and the adsorption data fitted well with the Langmuir isotherm model and pseudo-second-order kinetic model, indicating a mechanism of surface chemisorption. The adsorption capacities calculated based Langmuir isotherm model are 684.9 mg/g and 555.6 mg/g for the supported hydrozincite and Zn/Al-CO(3) (2−) hydrotalcite, respectively, higher than the adsorption capacities of other hydrotalcite-based adsorbents and most of other inorganic adsorbents reported previously. The XRD diffraction peaks of hydrozincite and Zn/Al-CO(3) (2−) hydrotalcite disappeared after the adsorption, and the Pb(II) species were uniformly dispersed in the adsorbents in form of Pb(3)(CO(3))(2)(OH)(2) proven by TEM, EDS mapping and XRD analysis, demonstrating the nature of the adsorption is the precipitation conversion of hydrozincite or Zn/Al-CO(3) (2−) hydrotalcite into Pb(3)(CO(3))(2)(OH)(2). These results demonstrate the synergic Pb(II) removal effect of the CO(3) (2−) and OH(−) derived from hydrozincite and Zn/Al-CO(3) (2−) hydrotalcite together with their ultra-thin thickness and high surface area contribute the excellent properties of the adsorbents. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s11671-017-2323-2) contains supplementary material, which is available to authorized users.